Efektivitas Bimbingan Klasikal Metode Game Based Learning Berbasis Digital dalam Meningkatkan Efikasi Diri Siswa - Nisa, Farihatun; Ris Sumaryani; Sigit Hariyadi (Universitas PGRI Kanjuruhan Malang, 2024)
This study aims to determine the effectiveness of classical guidance services using digital-based game-based learning methods to improve students' self-efficacy. This study is an action research on guidance and counseling. The subjects of the study were students of class VIII H of SMP Negeri 31 Semarang. Students' self-efficacy was measured using a self-efficacy scale which was then analyzed using descriptive analysis. The results of this study indicate that in the pre-cycle, the percentage of self-efficacy was 56%, then given action in cycle I, self-efficacy increased to 62%, and then followed up in cycle II, there was also an increase in the level of student self-efficacy to 67%. Thus, it can be concluded that classical guidance using digital-based game-based learning methods is effective in improving students' self-efficacy